Knee angle prediction during stair ascending gait of trans-femoral amputee: Neural networks application - Jutamat Pinitlertsakun (2018)
For the Trans-femoral (TF) amputee, the biomechanics of stair gait can be analyzed in only the stair descending. The information of stair ascending gait can be evaluated for only the normal side. The study with TF amputee mostly referred to the stair ascending by leading with the normal side rather than the prosthetic side as there was none of prosthesis can be the leading side to climb up the stair so none of TF amputee can make the step over step climbing up the stair. Since there was none of prosthesis can be the leading side to climb up the stair, none of TF amputee can make the step over step climbing up the stair and hence none of the stair ascending gait prediction model has been studied in transfemoral amputee, this study is aiming to figure out the stair gait ascending pattern in transfemoral amputee which imitated by the healthy person. Then, the neural network model is constructed to predict the knee angle during stair ascending, in which purpose to integrate into the controller of the prosthetic knee component to assist the stair ascending gait. ©2012 IEEE.